Антикоррозионная защита метизных деталей аварийно-спасательного оборудования гальванопокрытиями Ni-Sn 2. Фазовый состав, микроструктура и свойства покрытий - Reva, Ольга; Kuznetsov, Борис; Uglov, В.; Urbanovich, Е. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The research of dependence the phase composition, microstructure, physical and mechanical properties of the Ni-Sn coverings, synthesized by electrochemical sedimentation from solutions, from their chemical compound is carried out. The optimal conditions for obtaining electroplating alloys with high corrosion resistance are established; and reasonable prospects of their application to improve the reliability and the service life of tools and rescue vehicles.